Pengaruh Kualitas Pelayanan terhadap kepuasan Nasabah dalam Perspektif Ekonomi Islam (Studi Kasus pada Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan kantor Cabang Purwakarta) - Nurul Adimah; Irsyad; Wawan Oktriawan (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2022)
Everyone has the right to get social security in order to meet the basic needs of a decent life and increase their dignity. As a public service agency, the Employment Social Security Administering Agency (BPJS) which is non-profit, the quality of service is the starting point for its concentration. Quality services must always be provided in order to realize customer satisfaction and provide a good image in the community and provide a positive impact. The main objective of this study was to determine the effect of service quality and customer satisfaction in the perspective of Islamic Economics at BPJS Employment Purwakarta Branch Office. This research was conducted using a quantitative approach with the type of correlational research. The types of data are grouped into two categories, primary and secondary. Data collection techniques were carried out by means of interviews, questionnaires, and observations. The population in this study are BPJS Employment customers. The sampling technique used is simple random sampling technique obtained by 100 respondents. Furthermore, the data analysis technique used simple linear regression with the SPSS Statistics 22 application. The correlation results showed a value of = 0.845. Because the significance value = 0.845 > 0.05, thus the HO is rejected. Ha is accepted and it can be concluded that there is a correlation/relationship between the variables of service quality and customer satisfaction. Based on hypothesis testing, the ttable value is 1.984. So the value of tcount > ttable = 15,623 > 1,984. So it can be concluded that the service quality variable has a significant positive effect on the customer satisfaction variable. The contribution of the independent variable of service quality to the dependent variable of customer satisfaction is 71.1% while the remaining 19.9% ​​is influenced by other factors not examined in this study.